2017
DOI: 10.1177/0192513x17741920
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Caregiver Communication About Reproductive and Sexual Health and Sensitive Sex Topics

Abstract: Numerous studies examining parent–teen communication about sex (PTCS) have focused on reproductive and sexual health information (i.e., pregnancy, physical development, contraception), with significantly fewer addressing communication about sensitive sex topics (i.e., sexual pleasure, masturbation). This study compares predictors of communication about reproductive and sexual health to those of sensitive sex topics with early adolescents. Participants were 465 rural caregivers and their African American youth.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
32
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 32 publications
(34 citation statements)
references
References 61 publications
(87 reference statements)
2
32
0
Order By: Relevance
“…Our findings support previous research suggesting caregiver attitudes about sexual communication are critical to actual communication about sex (e.g., Ritchwood et al, in press). Additionally, results support studies suggesting that the quality of caregiver-adolescent communication about sex (e.g., open communication) is critical to reducing risky sexual behavior and often considered to be a good indicator of positive and proactive parenting (DeVore & Ginsburg, 2005; Wilson & Donenberg, 2004).…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…Our findings support previous research suggesting caregiver attitudes about sexual communication are critical to actual communication about sex (e.g., Ritchwood et al, in press). Additionally, results support studies suggesting that the quality of caregiver-adolescent communication about sex (e.g., open communication) is critical to reducing risky sexual behavior and often considered to be a good indicator of positive and proactive parenting (DeVore & Ginsburg, 2005; Wilson & Donenberg, 2004).…”
Section: Discussionsupporting
confidence: 90%
“…Despite the known benefits of caregiver-adolescent communication about sex, many caregivers of early adolescents fail to engage their youth in such conversations (Jerman & Constantine, 2010). Lack of such communication has been linked to low self-efficacy, unfavorable attitudes, and poor outcome expectations regarding communication about sex (Guilamo-Ramos, Jaccard, Dittus, & Collins, 2008; Lehr, Demi, DiIorio, & Facteau, 2005; Miller et al, 2009; Ritchwood et al, in press). For those who engage their youth in communication about sex, concerns have been raised about the limited range of topics typically covered during such discussions (Martin & Luke, 2010; Ritchwood et al, in press; Wyckoff et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Parental–child communication is of particular importance during adolescence. Communication provides a vehicle by which parents communicate their attitudes, values, and beliefs about a variety of topics including sex and sexuality to their children (Albert, 2009; Grossman, Jenkins, & Richer, 2018; Ikramullah, Manlove, & Cui, 2009; Ritchwood et al, 2018). Researchers who conducted a recent meta-analysis of 52 studies reported a significant positive association between parent–child sexual communication and adolescent safe sex behavior.…”
Section: Introductionmentioning
confidence: 99%